Import and Export of PhDs in Europe - sagara, takashi (Advances in Social Sciences Research Journal, 2015)
Education is recognized as one of the most significant knowledge-intensive export industries and its contribution to the trade balance cannot be ignored for many countries. Although there are a wide range of educational services for trade, this study focuses on the trade of ‘Doctoral Degrees’ or ‘Doctor of Philosophy (PhD)’ in Europe with a special emphasis on the top European universities in economics. By investigating the imports and exports of PhDs in the top European universities, this paper discovers that European countries have relatively distinctive roles in the trade of PhDs, net exporters (Belgium, Switzerland and Germany), trader in balance (the Netherlands) and net importers (Spain and Denmark), in terms of its top universities.